Sistematización de la experiencia vivida en el curso Montaje Interdisciplinar Teatro, Fiesta y Carnaval 2023-1 (2025)
This research work arises from the interest in understanding the didactic strategies and intercultural processes that were part of the creation process of the play Enigma Carnaval. Work presented as the final product of the course Interdisciplinary Assembly Theater, Party and Carnival 2023-1 of the Antonio Nariño University. This work reflects a creative process that seeks to link dance, theater and carnival, and that through interdisciplinarity, allows visualizing how diverse cultural celebrations such as the Carnival of Blacks and Whites, the Carnival of Barranquilla and some Mexican representations can be integrated into a single staging.